1972
DOI: 10.1246/bcsj.45.1022
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry Rule for Predicting Bond Distortions in Conjugated Hydrocarbons

Abstract: A symmetry rule for predicting molecular shapes which is based on the second-order Jahn-Teller effect has been applied to the predictions of bond distortions in a number of nonalternant hydrocarbons in their ground and electronically excited states. In spite of the very crude approximation that only the lowest-lying excited state plays a dominant role in determining the energetically most favorable nuclear displacement, a fairly clear-cut criterion for molecular-symmetry reduction was obtained. The actual type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1975
1975
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…6) shows the same tracking of the extremal eigenvector by the unique Heilbronner mode, although in this case the maximum eigenvalue bl p lies below the critical threshold, and indeed at equilibrium the molecule retains its C 2v symmetry. 5…”
Section: (Iv) Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…6) shows the same tracking of the extremal eigenvector by the unique Heilbronner mode, although in this case the maximum eigenvalue bl p lies below the critical threshold, and indeed at equilibrium the molecule retains its C 2v symmetry. 5…”
Section: (Iv) Limitationsmentioning
confidence: 99%
“…2,3 Criteria for predicting whether s or p electrons will win the energy-geometry competition have been developed. 4,5 The history of the evolution, defence, computational exploration and experimental verification of the p distortivity concept is recounted in comprehensive review articles 6,7 and will not be discussed in detail here.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in bond distances would be more difficult. For example, Nakajima has examined bond distortions in planar, polycyclic conjugated hydrocarbons (32). It is found that the first excited state must lie within 1.2 eV of the ground state to produce distortions of 0.1 A, or less.…”
Section: El + -] )mentioning
confidence: 99%
“…2). The lattice instability thus predicted for the heptafulvalene trianion radical is closely related with the pseudo-Jahn-Teller effect [20][21][22][23] as follows: in the RHF approximation, the ground state is of Big symmetry and the lowest excited doublet state is of Au symmetry, and both the states are nearly degenerate, the energy difference being calculated to be 0.050 eV. Thus, it is predicted that the Dah nuclear arrangement does not represent a minimum of the potential energy and a nuclear configuration with a lower symmetry (C2~) is more stable.…”
Section: Lattice Instabilitymentioning
confidence: 99%